High performance Insights from GPU version CatBoost - Ershov, Vasily (Computer Tools in Education, 2022)
In this paper we discus GPU implementation of open-sourced gradient boosting library CatBoost. This implementations shows the state-of-the-art performance among openly-available libraries and we want to share design insights and used algorithms.
Keywords: catboost; gpu; gbdt; gradient boosting; nvidia; hpc; machine learning